Catalytic Synthesis of Dibenzazepines and Dibenzazocines by 7‐Exo‐ and 8‐Endo‐Dig‐Selective Cycloisomerization. Issue 11 (3rd March 2021) - Ito, Mamoru; Takaki, Asahi; Okamura, Moeka; Kanyiva, Kyalo Stephen; Shibata, Takanori
Abstract: The 7‐ exo ‐ and 8‐ endo ‐ dig ‐selective gold‐catalyzed cycloisomerizations of 2‐propargylamino biphenyl derivatives were developed. The reaction of terminal alkynes gave dibenzo[ b, d ]azepines by 7‐ exo ‐ dig cycloisomerization. In contrast, when internal alkynes were subjected to the reaction, 8‐ endo ‐ dig cycloisomerization proceeded to provide dibenzo[ b, d ]azocines. The nucleophilicity at the reaction site and the electron‐withdrawing effect of a tosyl group were important for the present selective transformation. This protocol could be used for ynamide substrates and a silver‐catalyzed reaction gave 7‐ exo ‐ dig products selectively. Abstract : The cationic Au(I)‐catalyzed reaction achieved 7‐ exo ‐ dig ‐selective cycloisomerization of 2‐propargylamino‐ N ‐tosylbiphenyls with terminal alkyne along with the construction of a dibezazepine skeleton. In addition, the reaction of internal alkynes gave 8‐ endo ‐ dig ‐selective products. This strategy could be used for the ynamide substrate and the intramolecular reaction provided 7‐ exo ‐ dig ‐selctive cycloadducts by use of a Ag salt.